Cushing’s Syndrome (CS) in Children: Pathophysiology, Clinical Features, Diagnostic, and Therapeutic Strategies - Ashraf, Sana; Parveen, Shakeela; Ashraf, Saba; Batool, Uzma; Sultana, Mehwish; Ishaque, Urwah; Shafqat, Zainab; Shabbir, Saman; Riaz, Zainab; Faiz, Zunaira (BioScientific Review, 2023)
A rare condition known as Cushing’s Disease (CD) causes increased morbidity or mortality. It is an endocrine illness that presents differently from other endocrine disorders, making it difficult for doctors to control. Hence, early detection and treatment are essential. Significant fetal and mental complications during pregnancy are linked to Cushing’s Syndrome (CS). Except in the late trimester, surgery is its preferred method of treatment during pregnancy, with medication therapy as a backup. Therapeutic methods such as anti-cortisol medication, bilateral adrenalectomy, or radiation procedures may, therefore, be required to prevent long-term dangers of hypercortisolism, such as hirsutism, moon face, facial plethora, and obesity. Endogenous hypercortisolism increases the risk of cardiovascular metabolic symptoms, osteoporosis, respiratory diseases, psychological difficulties, and infections, while also inducing a high rate of morbidity or mortality.